2020
DOI: 10.2174/1874331502014010059
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Contract Farming to Small-scale Farmers in Africa and the Implications for Policy: A Review Scenario

Abstract: Introduction: Contract Farming (CF) has been largely believed to have the ability to promote the chances of Small-scale Farmers (SSFs) from less developed nations to participate in intensive agricultural production and lucrative export markets, thereby integrating them into the latest way of doing agri-business. Problem statement: A perennial issue of SSFs in Africa is a subsistence agricultural productivity due to lack of proper markets, credits and technology in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Incidentally, the auction system is plagued with uncertainties along most of the buyer and supplier performance metrics. This is evidenced by imprecise production quantities, unstable purchase prices that serendipitously swing from low prices to outrageously high prices, fuzzy quality standards, and erratic delivery schedules (Ncube, 2020). As an alternative to the auction system in 2004 the contract system was introduced in Zimbabwe.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Incidentally, the auction system is plagued with uncertainties along most of the buyer and supplier performance metrics. This is evidenced by imprecise production quantities, unstable purchase prices that serendipitously swing from low prices to outrageously high prices, fuzzy quality standards, and erratic delivery schedules (Ncube, 2020). As an alternative to the auction system in 2004 the contract system was introduced in Zimbabwe.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Contract farming has revolutionised the agriculture sector by improving agricultural productivity in both developing and developed countries. Realising the effectiveness of contract farming, non-government organisations, policy makers, donors, and researchers have proposed to governments, especially in developing countries, to promote and facilitate contract farming to enhance agricultural productivity [1][2][3][4][5]. Contract farming is a legal agreement between a producer (grower) and a buyer (agriculture firm) for a specific duration on predefined conditions, which offers agricultural inputs and economic resources to the producer, whereas the producer, in return, allows agricultural firms to control and educate farmers about the quality and quantity of agricultural product [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13]. Researchers, such as [2,[14][15][16][17][18][19][20], have shed light on the drawbacks of contract farming. Researchers, including [14][15][16][21][22][23][24][25] have reported that many farmers regret participating in contract farming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the marketing of agricultural products, farmer organizations increase farmer's bargaining power against buyers and intermediaries. Moreover, by acting collectively, farmers reduce marketing risks and transaction costs (Ncube, 2020) and have greater access to market information (Abu et al, 2016). These features will increase farmers' gains from selling their products and improve their welfare (Courtois and Subervie, 2014).…”
Section: Introductionmentioning
confidence: 99%